Spatio-Temporal Evaluation of Physicochemical Parameters, Heavy Metals, and Pesticides in the Little Zab River - Salih, Mamoon Q.; Tahir, Tara F.; Hamad, Wali M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Water quality is a fundamental determinant of human health, influencing the prevalence of waterborne diseases and the overall safety of potable water. Contaminated water sources expose populations to microbial pathogens and toxic chemical contaminants, presenting significant public health and environmental challenges. In this study, a comprehensive assessment of water quality was conducted on a segment of the Little Zab River, situated in the Kurdistan region of Iraq. Water samples were meticulously collected from five strategically selected sites along the river, spanning across all four seasons, to evaluate temporal variations in water quality. In situ measurements of critical physico-chemical parameters, including pH, electrical conductivity, total dissolved solids, salinity, dissolved oxygen, density, and turbidity, were performed to establish baseline water quality profiles. Concurrently, laboratory analyses were performed to quantify the concentrations of selected heavy metals (mercury, cadmium, arsenic, zinc, iron, lead, and copper) and pesticides (α-cypermethrin, acetamiprid, dichloro-diphenyl-trichloroethane, and p,p՛-DDD) using standardized methods. Descriptive statistical analyses, conducted using Excel and Statistical Package for Social Sciences, revealed significant spatial and seasonal fluctuations in both the physicochemical parameters and contaminant levels, with certain sites exhibiting concentrations that raise potential health and ecological concerns. The findings underscore the critical need for continuous monitoring of water used in agriculture and the implementation of targeted management strategies to mitigate contamination and protect public health in the region. This work contributes valuable insights into the interplay between natural processes and anthropogenic impacts on riverine water quality in arid and semi-arid environments.